A framework to monitor and evaluate the vulnerability of smallholder livestock farmers: a case study of Limpopo & Mpumalanga Provinces - Nesamvuni, Azwihangwisi E.; Tshikolomo, Khathutshelo A.; Lekalakala, Gabriel R.; Petja, Brilliant M.; van Niekerk, Johan (Technium Social Sciences Journal, 2022)
A study was carried out to assess the level of vulnerability of smallholder livestock farmers to provide appropriate support response to the changing climate. Central to the investigation was to develop a monitoring and evaluation framework with SMARTT indicators in the design, planning, implementation, assessment and evaluation of the vulnerability of smallholder livestock farmers. Fieldwork was conducted in both Limpopo and Mpumalanga provinces. Only Vhembe and Gert Sibanda District Municipalities were chosen based on the proximity and convenience of having Smallholder Livestock Farmers that were organized and within reach to the investigators. The sampling frame consisted of a database of village households owning livestock in Vhembe (4 municipalities) and Gert Sibande (7 municipalities) districts. Data was collected through a descriptive survey using structured questionnaires, observations, and interviews from individuals and focus groups. A structured questionnaire was developed where respondents were interviewed each being asked a standard set of questions posed in the same way each time. At least 469 small-holder farmers were interviewed using a semi-structured questionnaire to elicit responses on vulnerability. The questionnaire included among others demographic and economic household characteristics; livestock and crop production; access to extension services; credit access; hazards occurrence; adaptations strategies pursued; coping strategies; the level of resilience and other information as indicated in the methodology. This paper presents a theoretical and conceptual M&E framework while also positing that if such a framework is mainstreamed, it will enhance impact and outcomes. Informed by Lindoso (2011) the Framework for vulnerability assessment and adaptive response of smallholder livestock farmers, had three main attributes, namely: exposure, sensitivity, and adaptive capacity. Exposure as an attribute of vulnerability was the magnitude and frequency of the climate stimuli and was considered as an external property of socio-ecological systems. Indicators were developed under the thematic areas of aridity, drought, temperature, precipitation, wind and vegetation. Sensitivity was referred to as the degree to which a system is modified or affected by an internal or external disturbance or set of disturbances. The proposed thematic areas in which indicators were developed were involvement in smallholder livestock farming (%), access to water by both farmers (%) and livestock (%), distance to water sources by both SHF (%) and livestock (%), quantity & frequency of water – availability (%) and quantity (litres/ capita/ day), livestock water use efficiency (m3/annum), livestock production systems. Adaptive capacity was referred to as the ‘ability of socio-ecological systems to administer, accommodate, and recover from eventual environmental disturbances; it was assumed to be a function of wealth, technology, education, information, skills, and infrastructure, access to resources, and stability and management capabilities. He proposed thematic areas identified were demography of livestock farmers, product diversification, capacity building, access to electricity and financial support. Demographic factors had different influences on the capacity of smallholder livestock farmers to adapt to adverse effects of climate change and variability on the farming enterprises. An ideal SHAE should be one with a matric, have experience in the hands-on production of a particular commodity such as beef cattle, have received training in the commodity value chain and is not older than 60 years.